The Pediatric Neuroblastoma: Application of MIBG Scintigraphy in Diagnosis, Staging, and Follow-up – Analysis of Three Cases - Mohammed Otmane; Nadia Alaoui Ismaili (Swiss Journal of Radiology and Nuclear Medicine)
Introduction: Neuroblastoma is the most common extracranial solid tumor in children, accounting for 8-10% of all pediatric cancers. Accurate diagnosis and management rely on imaging modalities and biological markers such as elevated urinary catecholamines. Among the various imaging techniques, Metaiodobenzylguanidine (MIBG) scintigraphy, often combined with SPECT/CT, provides high specificity for neuroblastoma cells. It is crucial for determining tumor extent, identifying metastatic disease, and monitoring therapeutic response.